How Hercules cleans up the Augean stables: differentiated implementation of the EU Water Framework Directive - Duncan Liefferink (IWA Publishing, 2021)
Realising the goals of the European Union (EU) Water Framework Directive is difficult. The differentiation of water policies according to local conditions enjoys increasing attention and may be necessary to achieve good ecological status in all European waters. This paper seeks to explore to what extent and how local water quality determines the degree of coercion, i.e. the extent to which differentiated policies are voluntary or rather imposed upon policy addressees, of spatially differentiated water policies. It does so on the basis of seven cases in five EU Member States. For highly polluted waters, spatially differentiated policies tend either to make the use of authoritative policy instruments, i.e. coercion by way of formal regulation, or to rely on the threat to introduce such regulation. For preventing the deterioration of relatively ‘clean’ waters, voluntary instruments based on information and persuasion dominate, often supported by subsidies and/or the direct input of public resources. In relation to the spatial differentiation of water policies, issues of data demand, equality and legitimacy have to be taken into account. HIGHLIGHTS The paper explores the relationship between local water quality and policy instruments used for locally differentiated policies under the EU Water Framework Directive (WFD).; In case of a long distance to the WFD targets, instruments with a high degree of coercion, e.g. formal regulation, prevail.; If local quality is close to the WFD targets, lower degrees of coercion, e.g. information or subsidies, prevail.;